Determination of rational number suspensions of conveyor with suspended belt and distributed drive - Alexander Valer'evich Lagerev; Evgeniy Nikolaevich Tolkachev (Вестник СибАДИ, 2017)
The article is devoted to current issue related to the definition of a rational number of suspensions of conveyor with suspended belt and distributed drive. Using the basic design of the conveyor with suspended belt and distributed drive, a series of numerical calculations was performed. As a result, the influence of the number and ratio of types of suspensions on the main technical parameters of the conveyor was established. Recommendations on the choice of rational number of suspensions were formulated.